[LB.02.01] HOMA INDEX AS A PREDICTOR OF HYPERTENSION IN A PEDIATRIC OBESE POPULATION: PRELIMINARY RESULTS. (September 2017) - Pugno, A.; Zambelli, D.; De Benedetti, C.; Persampieri, S.; Vizzuso, S.; Verduci, E.; Banderali, G.; Carugo, S.
Abstract : Objective: Find predictors of hypertension in obese children diagnosed with ABPM and office BP Design and method: we studied 20 obese children (age 13 ± 0.9 ys, 11 M 9 F) enrolled in our Pediatric Division, with mean BMI of 30.3 ± 4.3, height 1.53 ± 0.11 and weight 72.2 ± 16.6. We evaluated a clinic visit, blood samples, blood pressure measurements (BP office mean of 3 measurements), 24 h ambulatory blood pressure (ABPM), echocardiogram and intimal media thickness (IMT) of common carotid artery. Results: Mean BP office was: systolic 121 ± 12 mmHg, diastolic 65 ± 10 mmHg; mean 24 h ABPM was: systolic 127 ± 10 mmHg and diastolic 70.2 ± 6.24 mmHg; diurnal systolic ABPM 121.9 ± 10.7mmHg, nocturnal 109.1 ± 10.5mmHg; diurnal diastolic ABPM: 75.1 ± 7.9 mmHg, nocturnal 62 ± 5.6 mmHg. For 24 h ABPM pediatric criteria, 2 patients were >90%percentile for sex, age and height for normal-high blood pressure values and 7 pt were>95% for hypertension criteria. Regardless percentile (%) BP criteria for children we observed that for systolic nocturnal BP 2 subjects were>90% and 7>95% and for diastolic BP 4 subjects>90% and 4 >95%. In general ABPM showed 11 patients as hypertensive, 7 were>95% for systolic and 2>95% only for diastolic. Considering predictors of arterial hypertension in our population we figured out that: (i) HOMA index has a positive correlation with systolic office BP (p = 0.03) and (ii) a borderline correlation with mean systolic ABPM (p = 0.06). Interestingly in our paediatric population, in patients defined as hypertensive for the 95% criteria with the ABPM monitoring, HOMA index was significantly different between hypertensive and non-hypertensive children (p = 0.05) Conclusions: In conclusion our preliminary report show that: (i) ABPM has a better sensitivity in diagnosing arterial hypertension versus office BP measurement and that (ii) HOMA index is an important predictor of hypertension in healthy obese children.